2014
DOI: 10.17221/553/2013-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Development of new cereal-, pseudocereal-, and cereal-leguminous-based probiotic foods

Abstract: Kocková M., Valík Ľ. (2014): Development of new cereal-, pseudocereal-, and cereal-leguminous-based probiotic foods. Czech J. Food Sci., 32: 391-397.The suitability of the selected cereals, pseudocereals, and legumes for new probiotic foods development was tested. Probiotic products were produced by inoculating buckwheat, dark buckwheat, barley, oat, soya, and chickpea in combination with oat with lactobacillus rhamnosus GG and subsequent moulding to eliminate water from the cooked grains. The cell growth, pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 13 publications
1
14
0
1
Order By: Relevance
“…Intensity of the total aroma ranged from 1.6 to 2.9 in single fermentation products representing moderate to strong intensity. Kocková and Valík () in their study reported a decrease of total aroma over the period of 21 days in a salted buckwheat product fermented by Lb . rhamnosus GG.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Intensity of the total aroma ranged from 1.6 to 2.9 in single fermentation products representing moderate to strong intensity. Kocková and Valík () in their study reported a decrease of total aroma over the period of 21 days in a salted buckwheat product fermented by Lb . rhamnosus GG.…”
Section: Resultsmentioning
confidence: 96%
“…The addition of buckwheat flour and oat bran improved the counts of probiotic bacteria when compared with the control ( P < 0.05). Additionally, several workers have indicated that buckwheat represents a good substrate for the growth and survival of probiotic bacteria, even in water‐based ones (Kocková & Valík, ; Liptáková, Petruláková, Pelikánová, Valík, & Krištúfková, ; Matejčeková, Liptáková, & Valík, ; Pelikánová, Liptáková, & Valík, ).…”
Section: Introductionmentioning
confidence: 99%
“…Table 4. Overview of traditional fermented products and beverages [7,135]. As an example, the growth of Fresco DVS 1010 culture at 37 °C and the survival of probiotic strain Lb.…”
Section: Fermented Cereal and Pseudocereal Food And Beveragesmentioning
confidence: 99%
“…The overall acceptability was evaluated from 2.80 to 3.30 (four-point scale) that indicated pleasant acceptance except caramel water mash (2.56). Kocková and Valík [135] noted negative effect of a 21-day storage period on overall acceptability buckwheat product with salt fermented by probiotic strain Lb. rhamnosus GG from values 3.31 to 2.44.…”
Section: Microorganismmentioning
confidence: 99%
“…The negative effect of storage on overall acceptability of fermented amaranth mashes was noted. Kocková and Valík (2014) also noted negative effect of 21 days storage period on overall acceptability buckwheat product with salt fermented by Lb. rhamnosus GG from value 3.31 to 2.44.…”
Section: Resultsmentioning
confidence: 86%